Trilogy of the Islamic Monetary System; Exploring the Proposits of Naqli as the Theological, Cosmological and Anthropological Basis of the Islamic Monetary System - Aris Fauzin; Sofyan Al-Hakim; Iwan Setiawan (al-Afkar, Journal For Islamic Studies, 2024)
This article discusses the Trilogy of Islamic Monetary System with a focus on the exploration of naqli postulates as the theological, cosmological, and anthropological foundations of the Islamic monetary system. In this research, a qualitative descriptive method is used. In this case, the analysis is carried out by digging and exploring the understanding of Islamic principles contained in the Qur'an and As-Sunnah as a guide to building a monetary system that is in accordance with the values of Islamic teachings. The research discussion in this article is focused on three perspectives, namely: Theological, cosmological, and anthropological perspectives. In the theological perspective, this article identifies key concepts such as the principle of tawhidullah, God as the regulator of human sustenance, and obedience to God's law as the foundation for designing a just monetary system. From a cosmological point of view, this research investigates the relationship between the Islamic monetary system and the order of the universe, outlining how the principles of Islamic economics reflect harmony with God's other creatures. Meanwhile, in the anthropological aspect, the article analyses how the Islamic monetary system pays attention to human needs and rights, creating social and economic balance. The study concludes that this trilogy of Islamic monetary system enlightens the importance of understanding and applying naqli postulates in designing a holistic monetary system, encompassing theological, cosmological, and anthropological dimensions to achieve balance and blessings in the economic life of Muslims.